Risk factors for sternal wound infections and application of the STS score in coronary artery bypass graft surgery - Farsky,Pedro Silvio (2011)
BACKGROUND: Sternal wound infection (SWI) after coronary artery bypass graft (CABG) surgery is a major complication. Identifying patients at risk of SWI is essential for the application of preventive measures. OBJECTIVE: To identify the pre- and intra-operative risk factors, apply the STS risk score and determine the correlation between the risk score and microorganisms isolated from surgical wounds in a Brazilian hospital. METHODS: This is a retrospective analysis of a database of all CABG surgeries performed in a single institution from 2006 to 2008. Chi-square analysis was used for categorical variables and Student's t-test was used for quantitative variables. Multivariate logistic regression model was used to identify independent risk factors for SWI. P <0.05 was considered significant. RESULTS: The infection rate was 7.2% (143/1975). The multiple regression analysis found the following risk factors: female gender (OR 2.06; 95%CI 1.40-3.03; P<0.001), BMI>40 kg/m² (OR 6.27, 95%CI 2.53-15.48; P<0.001), diabetes (OR 2.33; 95%CI 1.56-3.49; P<0.001), number of affected coronary arteries (OR 7.78; 95%CI 1.04-57.79; P<0.001) and use of bilateral internal thoracic artery (OR 3.85; 95%CI 2.10-7.07; P<0.001). Infected patients had a mean score of 9, whereas non-infected patients had a mean score of 7 (P<0.001). There was no correlation between microorganisms, scores and risk factors. CONCLUSION: Female gender, diabetes, BMI>40 kg/m², number of affected coronary arteries and use of bilateral internal thoracic artery were associated with a higher risk of infection. The STS risk score can be successfully used and there was no correlation between microorganisms, the score and risk factors at our institution.